Perancangan Sumber Daya Guru, Siswa, Perlengkapan untuk Pengajaran dan Pembelajaran Billingual - Pauziyyah, Afifah Intan; Ramadhani, Dini Asri; R, Rahmahyani; Arlani, Krisma Arisma Dwi; Lufiana, Rela; Widagdo, Arif (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The purpose of this study is to examine the design of bilingual learning resources that include three main components: teachers, students, and learning equipment. The type of method used is a literature study with a qualitative approach. The results of the study indicate that the success of bilingual learning is influenced by teacher competence, student readiness, and the availability of varied and adaptive learning equipment. The challenges faced include inequality in language ability, cognitive load, technological limitations, and lack of bilingual learning media. Therefore, resource design must be carried out comprehensively, integrated, and contextually so that bilingual learning can run effectively and inclusively.